The Risk of Rain. - Gorrie, Julian James (The IIE, 2022)
Shock marketing is a form of advertising/marketing strategy that intentionally shocks and offends its consumers by defying accepted societal norms. It is primarily intended to cut through dull and repetitious and recurrent content to draw attention to a particular issue, product, or service. The main argument of the study was to showcase that shock marketing could in fact be used as a method for both non-profit and for-profit organisations, regardless of operational capacity and scale to increase consumer attention surrounding the brand, its merchandise and activities, despite a positive or negative increase in brand image reception. The identified problem that the research aimed to fix was, that the existing waters of online content are too bountiful for the average consumer to ever engage with, let alone the capacity to retain it; thus, organisations need to rely on ultramodern tools and frameworks such as shock marketing to engage with their audience in order to ensure future success. The approach to this problem was the creation of online surveys, used to gather findings and insights that could be analysed quantitatively, which proved if shock marketing could be utilised to increase consumer attention compared to traditional methods. From the data analysis and findings, the supporting evidence suggested that the reactions towards shock marketing content were mixed, but often positive and gender did not play a major role in the overall result.
Keywords: Shock Marketing; Shock Advertising; Selective Perception; Traditional Marketing; Consumer attention; Consumer behaviour; Customer retention; Brand recall; Brand image; Non-profit; For-profit